Characterization of the elastic and viscoelastic properties of dentin by a nanoindentation creep test. Issue 10 (16th July 2015) - Chuang, Shu-Fen; Lin, Shih-Yun; Wei, Pal-Jen; Han, Chang-Fu; Lin, Jen-Fin; Chang, Hsien-Chang
Abstract Dentin is the main supporting structure of teeth, but its mechanical properties may be adversely affected by pathological demineralization. The purposes of this study were to develop a quantitative approach to characterize the viscoelastic properties of dentin after de- and re-mineralization, and to examine the elastic properties using a nanoindentation creep test. Dentin specimens were prepared to receive both micro- and nano-indentation tests at wet and dry states. These tests were repeatedly performed after demineralization (1% citric acid for 3 days) and remineralization (artificial saliva immersion for 28 days). The nanoindentation test was executed in a creep mode, and the resulting displacement–time responses were disintegrated into primary (transient) and secondary (viscous) creep. The structural changes and mineral densities of dentin were also examined under SEM and microCT, respectively. The results showed that demineralization removed superficial minerals of dentin to the depth of 400 μm, and affected its micro- and nano-hardness, especially in the hydrate state. Remineralization only repaired the minerals at the surface layer, and partially recovered the nanohardness. Both the primary the secondary creep increased in the demineralized dentin, while the hydration further enhanced creep deformation of untreated and remineralized dentin. Remineralization reduced the primary creep of dentin, but did not effectively increase the viscosity. In conclusion, water plasticization increases the transient and viscous creep strains of demineralized dentin and reduces load sustainability. The nanoindentation creep test is capable of analyzing the elastic and viscoelastic properties of dentin, and reveals crucial information about creep responses.